Institutional framework and financial arrangements for supporting the adoption of Resource Recovery Reuse technologies in South Asia - Maksud Bekchanov; Pablo Evia; Mohammad Monirul Hasan; Narayan Adhikari; Daphne Gondhalekar (University of Bonn, Center for Development Research (ZEF), 2018)
Open dumping of waste and discharging untreated wastewater into environment are key causes of environmental pollution in the developing world, including South Asian countries. Waste and wastewater however can be a source for recovering energy, nutrients and water if properly treated or recycled rather than a cause of pollution and diseases spread. The importance of adopting Resources Recovery and Reuse (RRR) technologies increases under growing demand for food and energy in contrast to depleting fossil fuel mines and groundwater reservoirs. However, institutional framework including the organizations and various stakeholders involved in the waste and wastewater management sectors, government policies and legislation, as well as financial arrangements and incentives to technological change play a pivotal role in adopting and scaling up RRR options. This study therefore focuses on institutional and financial aspects of challenges and opportunities for implementing RRR options in South Asia. It is argued that improving financial capacities, easing to obtain land use permits to expand RRR facilities, maintaining quality of RRR products (compost, biogas), and raising environmental awareness are imperative for the successful performance of the RRR projects in South Asia.
Keywords: O13; Q01; Q53; D02; Q58; Q20; 330; Resource Recovery and Reuse (RRR); organic waste; wastewater; alternative resources; environmental security; environmental policy